Absorbable Polymer Technology – Viable Solutions for Unmet Needs in PCI - (:unkn) unknown (My University, 2015)
The use of drug-eluting stents (DES) has improved clinical outcomes in percutaneous coronary intervention procedures, but many challenges remain. In two symposia at EuroPCR 2015, the factors necessary to ensure successful chronic total occlusion (CTO) intervention were presented. Good preparation, sufficient operator experience and the correct approach are key to the success of CTO interventions. A live case demonstrated the challenges of these complex cases. Stent choice in CTO interventions is crucial; second-generation DES are associated with lower rates of restenosis and re-occlusion compared with first-generation DES. The Coracto™ DES features unique structural properties and rapidly absorbable polymer, resulting in excellent conformability, efficacy and safety.
Keywords: chronic total occlusions; drug-eluting stent; Percutaneous coronary interventions